Frequency and Risk of Occupational Health and Safety Hazards for Home Healthcare Workers. (November 2017) - Suarez, Rassull; Agbonifo, Noma; Hittle, Beverly; Davis, Kermit; Freeman, Andrew
Given the increased prevalence of chronic disease and health care costs, more individuals are treated in the home, which has augmented the demand for more Home Healthcare Workers (HHCWs) in the field. HHCWs face multiple hazards with injury rates being more than double the national average; however, current studies on HHCWs have provided limited understanding of their occupational safety & health experiences and exposures. The aim of this study was to assess the frequency and risk of exposures through perceptions of HHCWs. The results of this study provide an initial picture of the different risks that HHCWs face daily. These findings show that studies involving HHCWs occupational safety need to be job-specific, and the proposed interventions will also likely need to be tailored by HHCWs type.